Use of remote sensing in native grass biomass modelling to estimate range productivity and animal performance in a tree-shrub savanna in southern Zimbabwe - Hassen, Abubeker (University of Pretoria, 2020)
Thesis (PhD (Animal Production Management))--University of Pretoria, 2020.